Muscle hypertrophy and serum hormone concentrations during combined strength and endurance training vs. strength or endurance training only in middle aged and older women - Jensen, Benjamin (2008)
Jensen, Benjamin 2008. Muscle hypertrophy and serum hormone concentrations during combined strength and endurance training vs. strength or endurance training only in middle aged and older women. University of Jyväskylä, Department of Biology of Physical Activity. Master’s thesis in Science of Sport Coaching and Fitness Testing. 70 pp. Purpose: The purpose of this investigation was to compare the effects of strength training only (2 x week), endurance training only (2 x week), and combined training (2 + 2 x week) on muscle hypertrophy and serum hormone concentrations in middle-aged and older women during 21 weeks of training. Methods: 96 healthy, moderately active middle-aged and older women were assigned to three training groups and a control group; 1) Strength training only (S, n = 27) 2 x week, program included dynamic exercises that activate a large amount of muscle bulk and increase energy metabolism. 2) Endurance training only (E, n = 26) 2 x week was performed by bicycle ergometer, heart rate levels of endurance training were determined by aerobic performance tests and monitored during training. 3) Combined strength and endurance training (SE, n = 25), performed both E and S sessions. 4) Control group (C, n = 18) was instructed to maintain their habitual physical activities which were monitored by training diaries. Lean mass (LM) of the legs and arms was measured by dual-energy x-ray absorptiometry (DEXA) and muscle thickness of several muscles by ultrasound at weeks 0, 10, and 21. Serum basal hormone concentrations of several anabolic hormones were measured at weeks -1, 0, 10, and 21. Results: The S and SE groups showed significant increases in LM in both arms and legs (S 1.6%, 1.4%, SE 2.1%, 4.0% respectively). All training groups showed significant increases (p<0.05, p<0.001) in LM legs, but only the S and SE groups showed increases in arms LM. S and SE groups showed the largest increases in muscle thickness in all muscles measured, with the SE group having the largest gains in the legs (vastus lateralis +vastus intermedius) 11.5%, biceps femoris long 8.3%) while the S group had the largest increases in arms (triceps brachii 10.0%, biceps brachii 7.1%). All training groups exhibited significant increases in serum testosterone (p<0.05, p<0.001). Conclusion: Combined strength and endurance training by cycling may be more effective than strength training alone for increasing muscle hypertrophy whether being measured by DEXA or ultrasound in middle aged and older women.